Construção de indicadores socioeducativos a partir da experiência museal no programa escola-ciência do museu de ciências e tecnologia da PUCRS - Giglio, Roberta (2021)
The present study aimed to identify possible socio-educational impacts of PROESC, promoted by MCT-PUCRS in participating school communities and social centers. In this sense, it sought to answer what are the possible socio-educational impacts through a Case Study as qualitative approach. For data collection, primarily were analyzed four year of visitation reports (2016-2019) filled by the institutions representatives who participated in PROESC, as well as the comments – speeches from educators present in the reports of the 2019. In addition, questionnaires were applied to a group of educators who participated in the Program during 2019. Therefore, the research subjects were teachers/educators from schools and social centers covered by PROESC. All data were compared through a triangulation (visitation reports, educator’s speeches and questionnaires) in order to materialize – based on indicators produced by this analysis – possible impacts of the Program on schools and social centers. In the present research, Discursive Text Analysis (ATD) was used as the data analysis method. From the analysis of the data, indicators were produced that substantiate and highlight the aspects of PROESC considered relevant in socio-educational terms. It was observed that indicators such as “Post-visit reports referring to PROESC”; “Engagement of students in educational activities”; “Interaction between educators and students with the mediation team”; “Deepening of scientific and museal aspects based on the participation of educators in the pre-visit activity”; “Experiencing through interaction with museum objects'' and “Content of the exhibition area with accessible and dynamic language”, show how PROESC’s activities enable a vision directed to elements that can contribute to the improvement of the museum experience related to science education, whose potential relates to a positive influence in terms of elaboration, organization and implementation of other social programs/projects that are - or can be - planned in non-formal education spaces such as MCT-PUCRS. These elements confirm the thesis that there is an impact on the institutions which use to offer to their students the possibility to visit the Museum; and that it becomes effective from a museum experience lived from the awakening to scientific knowledge, from the contextualization of production of new understandings about science and from affective relations that happen in this space, throughout the educational process.